Development and Validation of a Prognostic Index for Risk Stratification of Patients with Early Repolarization - Stavrakis, Stavros (Ann Noninvasive Electrocardiol, 2012)
Background: Early repolarization (ER) is associated with increased mortality in the general population. We sought to develop and validate a prognostic index (PI) of mortality in patients with ER. Methods: We identified 852 consecutive patients (mean age 49 ± 12 years) with ER (J‐point elevation ≥0.1 mV in inferior or lateral leads), from the VA electronic electrocardiogram (ECG) database. A random sample of age‐matched patients with normal ECG was used as control (n = 257). The initial cohort was randomly split into a derivation and a validation cohort (2/3 and 1/3 of patients, respectively). A PI was derived from the weighed sum of the regression coefficients of each independent risk factor in the final model using Cox regression analysis. Results: During a median follow‐up of 6.4 years, 170 patients died. ER was associated with increased mortality compared to control (HR 1.49, 95% CI 1.05–2.12; P = 0.03). Older age, lower body mass index, non‐African American race, current use of angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers or sulfonyureas, prolonged corrected QT (QTc), and higher ER amplitude independently predicted all‐cause mortality. Annualized mortality rates were 1.3%, 2.2%, and 3.7% in the low, intermediate, and high‐risk groups, respectively, in the derivation cohort (log rank P < 0.0001) and 0.8%, 1.9%, and 4.1% in the low, intermediate, and high‐risk groups, respectively, in the validation cohort (log rank P < 0.0001). Model discrimination was very good (c‐statistic = 0.85 and 0.80 for derivation and validation cohort, respectively). Conclusions: A PI derived from simple clinical and ECG characteristics predicts mortality in patients with ER and may be used clinically for risk stratification.